Cross-cultural adaptation, validation and reliability of the brazilian version of the Richmond Compulsive Buying Scale - Priscilla Leite; Bernard Rangé; Monika Kukar-Kiney; Nancy Ridgway; Kent Monroe; Rodolfo Ribas Junior; J. Landeira Fernandez; Antonio Egidio Nardi; Adriana Silva (Brazilian Journal of Psychiatry, 2013)
OBJECTIVE: To present the process of transcultural adaptation of the Richmond Compulsive Buying Scale to Brazilian Portuguese. METHODS: For the semantic adaptation step, the scale was translated to Portuguese and then back-translated to English by two professional translators and one psychologist, without any communication between them. The scale was then applied to 20 participants from the general population for language adjustments. For the construct validation step, an exploratory factor analysis was performed, using the scree plot test, principal component analysis for factor extraction, and Varimax rotation. For convergent validity, the correlation matrix was analyzed through Pearson's coefficient. RESULTS: The scale showed easy applicability, satisfactory internal consistency (Cronbach's alpha=.87), and a high correlation with other rating scales for compulsive buying disorder, indicating that it is suitable to be used in the assessment and diagnosis of compulsive buying disorder, as it presents psychometric validity. CONCLUSION: The Brazilian Portuguese version of the Richmond Compulsive Buying Scale has good validity and reliability